A Case Study Of Buddy Reading Among Three Year 4 Esl Students In A National Primary School - Low, Joyce Soong Ping (2014)
A study was conducted by incorporating tutors’ self-produced English reading materials, cross-age tutoring and cooperative learning in Buddy Reading to be demonstrated as a viable method to sustain students’ interest towards English reading. Suatu kajian tentang pembacaan berkumpulan yang berunsur penggunaan bahan bacaan yang direka oleh tutor, tutor bersilang-usia dan pembelajaran koperatif telah dijalankan untuk mengekalkan minat pelajar untuk membaca dalam Bahasa Inggeris